2022
DOI: 10.1093/molbev/msac024
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Mutations Accumulate Faster in Allopolyploid Than Diploid Cotton (Gossypium) and Unequally between Subgenomes

Abstract: Whole genome duplication (polyploidization) is among the most dramatic mutational processes in nature, so understanding how natural selection differs in polyploids relative to diploids is an important goal. Population genetics theory predicts that recessive deleterious mutations accumulate faster in allopolyploids than diploids due to the masking effect of redundant gene copies, but this prediction is hitherto unconfirmed. Here, we use the cotton genus (Gossypium), which contains seven allopolyploids derived f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 77 publications
(114 reference statements)
1
17
0
Order By: Relevance
“…This is especially true for the older allopolyploids (i.e., cotton, wheat, and quinoa). Importantly, we expected that the subgenome with the more closely related diploid model (i.e., lower d S ) would exhibit artificially inflated d N (and therefore ω ) relative to the other subgenome due to the persistence of slightly deleterious changes, as well as the masking effect acting on recessive deleterious changes in the allopolyploids ( Conover and Wendel 2021 ). This is indeed the case for wheat, cotton, and tobacco, in which the subgenome with the more closely related diploid progenitor ( fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true for the older allopolyploids (i.e., cotton, wheat, and quinoa). Importantly, we expected that the subgenome with the more closely related diploid model (i.e., lower d S ) would exhibit artificially inflated d N (and therefore ω ) relative to the other subgenome due to the persistence of slightly deleterious changes, as well as the masking effect acting on recessive deleterious changes in the allopolyploids ( Conover and Wendel 2021 ). This is indeed the case for wheat, cotton, and tobacco, in which the subgenome with the more closely related diploid progenitor ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…6 ). This potentially indicates that the species of higher ploidy may inherently have higher ω due to mutations at phylogenetically conserved sites accumulating more rapidly in the polyploid subgenomes as a result of mutational masking ( Conover and Wendel 2021 ). The extent to which the evolutionary trajectory of polyploid lineages is affected by the accelerated accumulation of deleterious mutations, therefore, represents an important open question in plant biology.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, after polyploidization/ whole-genome duplication (WGD), some of the redundant genes were lost over the course of a few million years (Lynch and Conery, 2000). The most recent evolutionary analysis on the Gossypium genus reported that disrupted genes, also termed genes with deleterious mutations, have accumulated faster in allotetraploid cotton than in diploid species (Conover and Wendel, 2022). However, the precise effects of these disrupted genes on fibre traits have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…For the diploid W1 and E, the difference in diversity could be the results of refugia preservation during past repeated glaciations in the western mountains and degraded habitat in the east. Higher diversity in W2 may be due to genome duplication because tetraploids can have up to four alleles and hence a greater capacity to mask recessive mutations than diploid populations, and also to accumulate more neutral mutations (Bever & Felber, 1992; Conover & Wendel, 2022; Hill, 1970). Gene exchange with other species could also contributed to its diversity (Figure 3a; Figure S9).…”
Section: Discussionmentioning
confidence: 99%